Karakter Mikologi (Ahli Jamur) yang Diperankan Christine Hakim dalam TV Series “The Last of Us” - Marshanda Aulia Purnomo Putri; Alex Sobur (UNISBA Press, 2023)
Abstract. This study discusses the character of the mycologist or mushroom expert played by Christine Hakim in the TV series